Is the use of oral creatine supplementation safe? - Bizzarini, E.; De Angelis, L. (The Journal of Sports Medicine and Physical Fitness, 2004)
This review focuses on the potential side effects caused by oral creatine supplementation on gastrointestinal, cardiovascular, musculoskeletal, renal and liver functions. No strong evidence linking creatine supplementation to deterioration of these functions has been found. In fact, most reports on side effects, such as muscle cramping, gastrointestinal symptoms, changes in renal and hepatic laboratory values, remain anecdotal because the case studies do not represent well-controlled trials, so no causal relationship between creatine supplementation and these side-effects has yet been established. The only documented side effect is an increase in body mass. Furthermore, a possibly unexpected outcome related to creatine monohydrate ingestion is the amount of contaminants present that may be generated during the industrial production. Recently, controlled studies made to integrate the existing knowledge based on anecdotal reports on the side effects of creatine have indicated that, in healthy subjects, oral supplementation with creatine, even with long-term dosage, may be considered an effective and safe ergogenic aid. However, athletes should be educated as to proper dosing or to take creatine under medical supervision.